2023
DOI: 10.1186/s12889-023-15214-9
|View full text |Cite
|
Sign up to set email alerts
|

Undernutrition among the children below five years of age in Uganda: a spatial analysis approach

Abstract: Background Undernutrition is a health condition caused by a lack of enough food intake, not having enough of the right combination of food nutrients, or the body’s failure to utilize the food eaten resulting in either, stunting, being underweight, or wasting. Globally, undernutrition affects more than 149 million under-five children, while in Uganda about 3 in every 10 children suffer from undernutrition. Undernutrition and its risk factors among under-five children in Uganda were unevenly dist… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
11
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(11 citation statements)
references
References 15 publications
0
11
0
Order By: Relevance
“…This nding is supported by analogous studies conducted in Ethiopia and Uganda, which reported comparable results. 33,34…”
Section: Discussionmentioning
confidence: 99%
“…This nding is supported by analogous studies conducted in Ethiopia and Uganda, which reported comparable results. 33,34…”
Section: Discussionmentioning
confidence: 99%
“…Undernutrition is a common problem in Hoima in Hoima district. A study conducted in Kahoora division reported that stunting, underweight, wasting, and overweight was observed among 19.4%, 10.4%, 6.7%, and 3.3% of study participants respectively [22]. However, the prevalence and factors associated with anemia among children admitted at Hoima regional referral hospital is not known.…”
Section: Introductionmentioning
confidence: 93%
“…Poverty plays a crucial role in driving hunger and malnutrition, leading to inadequate food access and malnutrition (Katona & Katona-Apte, 2008), which in turn, results in severe health repercussions and diminished productivity. Notably, malnutrition affects 149 million children globally, leading to stunting and wasting (Maniragaba et al, 2023). Extreme weather events exacerbate food insecurity, amplifying the urgency for SDGs driven solutions.…”
Section: Introductionmentioning
confidence: 99%